Influencia de la enseñanza de las técnicas grafo plásticas para desarrollar la motricida fina en los niños y niñas del centro de Educación Inicial Las Ardillitas y la Escuela de Educación Básica Presidente Jaime Roldos Aguilera de la ciudad de Machala año lectivo 2012-2013. - Valdiviezo Martínez, Sonia Beatriz (2013)
Significant learning, autonomous learning, social constructionism and competency training, aims to support the training and updating of professionals in Early Childhood and Early Childhood Education to expand their knowledge and skills in their area of ​​specialization.